2021
DOI: 10.1038/s41598-021-87278-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the gene transcription patterns and DNA methylation characteristics of triploid sea cucumbers (Apostichopus japonicus)

Abstract: Breeding of polyploid aquatic animals is still an important approach and research hotspot for realizing the economic benefits afforded by the improvement of aquatic animal germplasm. To better understand the molecular mechanisms of the growth of triploid sea cucumbers, we performed gene expression and genome-wide comparisons of DNA methylation using the body wall tissue of triploid sea cucumbers using RNA-seq and MethylRAD-seq technologies. We clarified the expression pattern of triploid sea cucumbers and foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 57 publications
2
13
0
Order By: Relevance
“…S6 ). This outcome is consistent with that of Han (Han et al 2021 ). The measurement results revealed that the proportions of triploid A. japonicus in the 12–18- and 6–12-cm groups were higher than those in the diploid control group (Fig.…”
Section: Results and Analysissupporting
confidence: 92%
See 4 more Smart Citations
“…S6 ). This outcome is consistent with that of Han (Han et al 2021 ). The measurement results revealed that the proportions of triploid A. japonicus in the 12–18- and 6–12-cm groups were higher than those in the diploid control group (Fig.…”
Section: Results and Analysissupporting
confidence: 92%
“…During the breeding process, the water was changed every 2 days, and feeding was done once a day (feed formula: sea mud, compound feed, spirulina powder, purslane powder). We used flow cytometry (Sysmex, Japan) to determine the ploidy of A. japonicus , and the procedure was the same as Han’s (Han et al 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations